Zimbabwe Mbira Music on an International Stage: Chartwell Dutiro's Life in Music, Edited by Cartwell Dutiro and Keith Howard, SOAS Musicology Series, Ashgate: London. 2007, 98 pages, with CD: "Taanerimwe”, Chartwell Dutiro with Spirit Talk Mbira Live at Gateway (Gateway, SOAS Cat.No. SOASIS - 03), Hardbound: ISBN-13: 978-0-7546-5799-6. - Tracey, Andrew (International Library of African Music, 2008)
pages: 120-122
Keywords: Mbira music; Mbira; Musical instruments; African Music; Mbira (Instrument); Zimbabwe